Understanding E-Learning Satisfaction Through Technology Acceptance Model: A Case Study of Edlink Implementation at Sahid University - Kania Ratnasari; Rama Chandra; Didit Haryadi; R. Madhakomala (Green Publisher, 2025)
Good electronic resources and student-lecturer interaction are essential to improve student satisfaction during online learning; e-learning satisfaction is a multifaceted construction that significantly affects student engagement and retention in online learning environments. This study aims to examine and evaluate a four-variable model, including E-learning, Perceived Ease of Use, E-learning Satisfaction, and Perceived Usefulness. Quantitative methods are used to test scales, research models, and hypotheses. These include testing scale reliability, testing the validity and consistency of the scale, and Structural Equation Modeling (SEM) for hypothesis testing. The sample used was an active student of the Faculty of Economics and Business in the odd semester of 2023/2024 who had used Edlink at Sahid University. The object was chosen because Sahid University has an e-learning site, namely Edlink, that supports teaching and learning activities and is already running. One hundred thirty-eight questionnaires were distributed directly through Google Forms to students who had used Edlink. The data analysis technique in this study uses SEM with SmartPLS version 4. Through the evaluation of the measurement model with a loading factor of >0.70, Composite Reliability > 0.70, Cronbuc's Alpha >0.70 and Average variances Extracted >0.50. Then, we use the hypothesis test with Bootstrapping to determine the direct and indirect influences. The results of the study showed that there was an Effect of Perceived Ease of Use on E-learning satisfaction, No Effect of Perceived Usefulness on E-learning satisfaction, Effect of E-Lerning on Perceived Ease of Use, Effect of E-Lerning on Perceived Usefulness, Perceived Ease of Use did not mediate the Effect of E-Lerning on E-learning satisfaction, Perceived Usefulness mediated the Effect of E-Lerning on E-learning satisfaction.